Ten Epidemiological Parameters of COVID-19: Use of Rapid Literature Review to Inform Predictive Models During the Pandemic - Gallo, Luciana Guerra; Oliveira, Ana Flávia de Morais; Abrahão, Amanda Amaral; Sandoval, Leticia Assad Maia; Martins, Yure Rodrigues Araújo; Almirón, Maria; dos Santos, Fabiana Sherine Ganem; Araújo, Wildo Navegantes; de Oliveira, Maria Regina Fernandes; Peixoto, Henry Maia (Frontiers in Public Health, 2020)
Objective: to describe the methods used in a rapid review of the literature and to present the main epidemiological parameters that describe the transmission of SARS-Cov-2 and the illness caused by COVID-19. Methods: this is a methodological proposal that enabled a rapid review of COVID-19 epidemiological parameters. Findings: The proposal consisted of the following steps: definition of scope; eligibility criteria; information sources; search strategies; selection of studies; and data extraction. Four reviewers and three supervisors conducted this review in 40 days. 1,266 studies were found. Of these, 65 were included, mostly observational descriptive, indicating relative homogeneity as to the quality of the evidence. Stands out the variation in the basic reproduction number, between 1.32 and 14.8; and the median of the hospitalization period, between seven and 20 days. Conclusion: We have identified and synthesized 10 epidemiological parameters that may support predictive models and other rapid reviews in this and future public health emergencies.